2020
DOI: 10.3389/fmicb.2020.565767
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Evidence for Distinct Functions of Peptidoglycan Endopeptidases in Escherichia coli

Abstract: Peptidoglycan (PG) is an essential component of the bacterial exoskeleton that plays a pivotal role in the maintenance of cell shape and resistance to cell lysis under high turgor pressures. The synthesis and degradation of PG must be tightly regulated during bacterial cell elongation and division. Unlike enzymes involved in PG synthesis, PG hydrolases show high redundancy in many bacteria including Escherichia coli. In this study, we showed that PG endopeptidases have distinct roles in cell growth and divisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(50 citation statements)
references
References 33 publications
2
46
0
Order By: Relevance
“…This result is consistent with data from a previous report (Singh et al, 2012). In a previous study, we found a salt-sensitive phenotype in the mepM mutant (Park et al, 2020). A similar reversion of the phenotype was detected in the salt-sensitive phenotype of the mepM mutant (Figure 1C); the salt-sensitive phenotype of the mepM mutant was not observed in the M9 minimal medium.…”
Section: Meps and Mepm Are Not Necessary For E Coli Growth In M9 Minimal Mediumsupporting
confidence: 93%
See 3 more Smart Citations
“…This result is consistent with data from a previous report (Singh et al, 2012). In a previous study, we found a salt-sensitive phenotype in the mepM mutant (Park et al, 2020). A similar reversion of the phenotype was detected in the salt-sensitive phenotype of the mepM mutant (Figure 1C); the salt-sensitive phenotype of the mepM mutant was not observed in the M9 minimal medium.…”
Section: Meps and Mepm Are Not Necessary For E Coli Growth In M9 Minimal Mediumsupporting
confidence: 93%
“…In a previous study, we found an EDTA-sensitive phenotype in the mepS mutant (Park et al, 2020). This phenotype was restored by the overexpression of MepH, PbpG, and MepM, as well as MepS.…”
Section: Mepm Is An Nlpi-independent Substrate Of Prcmentioning
confidence: 75%
See 2 more Smart Citations
“…In some cases, apparently redundant PG enzymes can be distinguished by differences in substrate specificity (10,11), subcellular localization (12)(13)(14), and interaction partners (13,(15)(16)(17)(18). Additionally, recent work from our group and others revealed the activity of certain "redundant" PG synthases and autolysins changes based on the physiochemical properties of the growth medium (19)(20)(21)(22)(23)(24)(25). We discovered two semi-redundant E. coli PG synthases, PBP1a and PBP1b, are preferentially required for PG integrity in opposing pH environments, in part due to pH-dependent differences in enzymatic activity (21).…”
Section: Introductionmentioning
confidence: 99%